2020
DOI: 10.1038/s41598-020-69815-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical risk analysis of metals toxicity in wastewater irrigated soil and crops: a study of a semi-arid developing region

Abstract: Toxic elemental exposure through consumption of contaminated crops is becoming a serious concern for human health. Present study is based on the environment and health risk assessment of wastewater irrigated soil and crops in a semi-arid region Faisalabad, Pakistan. The concentrations of potentially toxic elements (Cu, Cr, Mn, Fe, Pb, Zn, Ni) were analysed by atomic absorption spectrometer in five different crops (Corn, rice, wheat, sugarcane and millet), while, their topsoil’s and multi targeted risks analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 53 publications
0
20
1
Order By: Relevance
“…Heavy metals mostly refer to metals and metalloids with high atomic weights. Some heavy metals, such as Cu, Pb, Hg, Cd, and Cr, can seriously affect the wellbeing organisms (Duan et al, 2020;Mahfooz et al, 2020). Many of these contaminants are able to sorb onto microplastics.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals mostly refer to metals and metalloids with high atomic weights. Some heavy metals, such as Cu, Pb, Hg, Cd, and Cr, can seriously affect the wellbeing organisms (Duan et al, 2020;Mahfooz et al, 2020). Many of these contaminants are able to sorb onto microplastics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of treated wastewater (TWW) for agricultural irrigation has gained global attention since water consumption has significantly increased due to the growing demand for food [ 4 ]. Currently, around 20 million hectares are irrigated with TWW in 50 countries, contributing to 40% of the food produced [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that the use of TWW can improve physicochemical properties and enhance the productivity of many economically important crops [ 5 , 16 , 17 ]. For example, the use of TWW enhanced the chlorophyll content, photosynthetic efficiency, and forage yield in alfalfa ( Medicago sativa ) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This polymer is extracted by treating seaweeds with sodium carbonate solution, where alginic acid is precipitated and sodium salt is formed. In addition, alginate products are known to have high sorption uptake, abundance, high selectivity, and no toxic effects (He & Chen, 2014 ; Li et al, 2021 ). Several studies revealed that sodium alginate is an efficient candidate for heavy metals adsorption such as Cu 2+ , Cd 2+ , and Pb 2+ (Gao et al, 2020 ; Qamar et al, 2022 ; Refaay et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%